(untitled) (Contemporary Journal of Social Science Review, 2026)
Purpose: The study aimed to identify the emotional health problems experienced by the librarians in university libraries of Pakistan, and measure the influence of emotional health problems and occupational stressors on job performance of librarians in university libraries. Methodology: Quantitative research method was applied to collect and analyze data. The study’s population was university librarians from public and private higher education commission (HEC) recognized universities in Punjab, Pakistan. A simple random sampling technique was adopted for data collection. Tool of questionnaire was applied to gather data from the target population. SPSS software was used for the analysis of gathered data. Results: Findings of the study revealed that university librarians generally experience positive emotional states, low levels of anxiety and stress, and positive attitudes toward their work. Overall, the study indicates a relatively healthy and satisfied workforce in the university libraries. The results indicated that there were no statistically significant relationships between the demographic variables and the presence of diagnosed emotional health illnesses among university librarians. It’s essential for institutions to continue monitoring and supporting the emotional well-being of their librarians to ensure a healthy and productive work environment. Originality: The study has provided valuable theoretical, practical and social implications. It has added a substantial amount of literature in existing body of knowledge. It has provided strategies for management bodies to consider emotional health of librarians for attaining fruitful outcomes at workplace.